Wars of the Roses : Margaret of Anjou - Iggulden, Conn (Iggulden, Conn. Wars of the Roses., 2015)
"The brilliant retelling of the Wars of the Roses continues with Margaret of Anjou, the second gripping novel in the new series from historical fiction master Conn Iggulden. As Traitors Advance...A Queen Defends. It is 1454 and for over a year King Henry VI has remained all but exiled in Windsor Castle, struck down by his illness, his eyes vacant, his mind a blank. His fiercely loyal wife and Queen, Margaret of Anjou, safeguards her husband's interests, hoping that her son Edward will one day come to know his father. With each month that Henry is all but absent as king, Richard, the Duke of York, Protector of the Realm, extends his influence throughout the kingdom. The Trinity--Richard and the earls of Salisbury and Warwick--are a formidable trio, and together they seek to break the support of those who would raise their colors and their armies in the name of Henry and his Queen. But when the king unexpectedly recovers his senses and returns to London to reclaim his throne, the balance of power is once again plunged into turmoil. The clash of the Houses of Lancaster and York may be the beginning of a war that can tear England apart. Following on from Stormbird, Margaret of Anjou is the second epic installment in master storyteller Conn Iggulden's new Wars of the Roses series. Fans of Game of Thrones and The Tudors will be gripped from the word "go." "--